Crystal Structure and Catalytic Activity of A Novel Cd(II) Coordination Polymer Formed by Dicarboxylic Ligand - Zhi Xiang Ji; Peng Fei Li (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
A new Cd(II) coordination polymer, {[Cd3(L)2(DMF)2(H2O)2]·H2O}n (H2L = 1,3-bisbenzyl-2-imidazolidine-4,5-dicarboxylic acid) was synthesized by one-pot synthesis method from 1,3-bisbenzyl-2-imidazolidine-4,5-dicarboxylic acid, NaOH, DMF, and Cd(NO3)2·4H2O. Its structure was determined by elemental analysis and single crystal X-ray diffraction. Structural analysis shows that three Cd(II) ions are all six-coordinated with four oxygen atoms of four 1,3-bisbenzyl-2-imidazolidine-4,5-dicarboxylate ligands and two O atoms from two DMF molecules (Cd1) or two oxygen atoms of two coordinated H2O molecules (Cd2 and Cd3) to form an octahedral coordination geometry. The Cd(II) coordination polymer displays a 1D chained structure by the bridging carboxylate groups from 1,3-bisbenzyl-2-imidazolidine-4,5-dicarboxylate ligands. The conversion of benzaldehyde is 90.9%, which is 40~50% higher than those of the other three aldehydes (4-methylbenzaldehyde, p-methoxybenzaldehyde and 3-chlorobenzaldehyde), so the Cd(II) coordination polymer catalyst shows better catalytic activity for the coupling reaction of benzaldehyde, phenylacetylene, and piperidine than the other three aldehydes.